Prevention of Nausea and Vomiting in Oncology - AV Snegovoi; VB Larionova; IB Kononenko; LV Manzyuk; AI Saltanov; VYu Sel’chuk (Клиническая онкогематология)
Background & Aims. Despite significant progress achieved over last 25 years, nausea and especially vomiting remain basic side effects of chemotherapy affecting patients’ quality of life. Modern antiemetic therapy permits to reduce the frequency of acute vomiting to 20–30 %, whereas the effectiveness of nausea prevention is higher. Available domestic publications do not describe fundamentals of the antiemetic therapy during treatment with cytostatic agents. The objective of this study is to evaluate the effectiveness of itopride in combined antiemetic therapy for prevention of acute nausea and vomiting, as well as in single drug therapy for arresting delayed vomiting.